2015
DOI: 10.1002/stem.1977
|View full text |Cite
|
Sign up to set email alerts
|

Brain Vascular Pericytes Following Ischemia Have Multipotential Stem Cell Activity to Differentiate Into Neural and Vascular Lineage Cells

Abstract: Brain vascular pericytes (PCs) are a key component of the blood-brain barrier (BBB)/neurovascular unit, along with neural and endothelial cells. Besides their crucial role in maintaining the BBB, increasing evidence shows that PCs have multipotential stem cell activity. However, their multipotency has not been considered in the pathological brain, such as after an ischemic stroke. Here, we examined whether brain vascular PCs following ischemia (iPCs) have multipotential stem cell activity and differentiate int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

27
223
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(251 citation statements)
references
References 65 publications
27
223
0
1
Order By: Relevance
“…However, reprogramming has been reported to cause adult brain pericytes to become non-pericytic lineages, such as neuronal lineages (10). In support of this notion, we showed that adult brain pericytes, which do not possess stem cell activity under normal conditions, reacquired stemness in response to ischemia, presumably through cellular reprogramming by mesenchymal-epithelial transition (11,12). We also showed that PDGFRβ + cells isolated from ischemic areas, including the leptomeninges, have a multipotent stem cell activity that gives rise to neuronal cells (11,12).…”
supporting
confidence: 79%
See 2 more Smart Citations
“…However, reprogramming has been reported to cause adult brain pericytes to become non-pericytic lineages, such as neuronal lineages (10). In support of this notion, we showed that adult brain pericytes, which do not possess stem cell activity under normal conditions, reacquired stemness in response to ischemia, presumably through cellular reprogramming by mesenchymal-epithelial transition (11,12). We also showed that PDGFRβ + cells isolated from ischemic areas, including the leptomeninges, have a multipotent stem cell activity that gives rise to neuronal cells (11,12).…”
supporting
confidence: 79%
“…In support of this notion, we showed that adult brain pericytes, which do not possess stem cell activity under normal conditions, reacquired stemness in response to ischemia, presumably through cellular reprogramming by mesenchymal-epithelial transition (11,12). We also showed that PDGFRβ + cells isolated from ischemic areas, including the leptomeninges, have a multipotent stem cell activity that gives rise to neuronal cells (11,12). Therefore, we proposed that brain pericytes localized along the leptomeninges to cortical parenchyma are likely the origin of leptomeningeal stem cells.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…After acute ischemia, proliferation of these, and other, progenitor cells in the CNS is enhanced [88,136,137], and, similarly, shorter pulses of ischemia to induce preconditioning effects also result in the proliferation of progenitors [137,138], with an increase of up to 4-fold observed after preconditioning in one study [137]. Interestingly, when proliferation was attenuated by administration of methylazoxymethanol acetate or ganciclovir, the preconditioning effect of a short ischemic event (15 min MCAO) was abolished [137]. These data suggest that the proliferation of progenitors is an effector of IPC-mediated neuroprotection.…”
Section: Progenitor Cellsmentioning
confidence: 99%
“…Although some of these proliferative cells in the hippocampus may differentiate into NeuN + cells [138], the identity of other proliferating cells in different regions of the brain has not been fully determined, but there is evidence that microvascular pericytes proliferate in response to ischemia [139], as do reactive astrocytes [140]. We have observed in a model of IPC (15 min MCAO) that the number of microglia substantially and significantly increases in the ipsilateral hemisphere of a preconditioned mouse (Fig.…”
Section: Progenitor Cellsmentioning
confidence: 89%